P2X7 receptor regulates osteoclast function and bone loss in a mouse model of osteoporosis - Ning Wang (Nature Portfolio, 2018)
Abstract Post-menopausal osteoporosis is a condition that affects millions worldwide and places a huge socio-economic burden on society. Previous research has shown an association of loss of function SNPs in the gene for the purinergic receptor P2X7R with low bone mineral density, increased rates of bone loss and vertebral fractures in post-menopausal women. In this study we use a mouse model of oestrogen deficiency-induced bone loss and the BALB/cJ P2X7R−/− to show that absence of the P2X7R resulted in increased bone loss. Osteoclast precursors were isolated from both BALB/cJ P2X7R−/− and BALB/cJ P2X7R+/+ mice and then cultured in vitro to form mature resorbing osteoclasts. The BALB/cJ P2X7R−/− derived precursors generated slightly more osteoclasts but with a significant reduction in the amount of resorption per osteoclast. Furthermore, when using modified culture conditions osteoclast activity was additionally increased in the absence of the P2X7R suggest that P2X7R may regulate the lifespan and activity of osteoclasts. Finally using mechanical loading as an anabolic stimulus for bone formation, we demonstrated that the increased oestrogen-deficient bone loss could be rescued, even in the absence of P2X7R. This study paves the way for clinical intervention for women with post-menopausal osteoporosis and P2XR7 loss of function polymorphisms.